Penerapan Psak No.16 Atas Aset Tetap Dan Hubungan Dengan Perhitungan Laba Pada Pt Garuda Indonesia.Tbk - Ma’ruf Dwi Putra; Ahmad Lintang Abdul Haq; Muhammad Yusuf Arda Bily (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
In service industries, trading companies and manufacturing industries, fixed assets are used in business activities. Every decision regarding the use of fixed assets affects the survival and development of a company. This not only considers the profits generated by a company, but also the important role of fixed assets in achieving company goals. Therefore, PSAK No.16 must be applied. Based on the data described above, the aim of this research is to confirm the application of PSAK no. 16 which is used to calculate the profits of the company PT. Garuda Indonesia Airlines. As a research method, we use descriptive analysis methods to understand existing facts and compare them with existing theories. To obtain the necessary data, the author uses data collection techniques such as documentation. The type of data used by the author is secondary data. From the research analysis, the author can conclude that the company has implemented fixed assets in accordance with PSAK No.16 (revised 2007). Companies use two methods to value fixed assets: the historical cost method and the revaluation model. The use of these two methods can affect the growth of fixed assets.